2023
DOI: 10.3390/polym15112473
|View full text |Cite
|
Sign up to set email alerts
|

Additive Manufacturing of Polymer/Bioactive Glass Scaffolds for Regenerative Medicine: A Review

Abstract: Tissue engineering (TE) is a branch of regenerative medicine with enormous potential to regenerate damaged tissues using synthetic grafts such as scaffolds. Polymers and bioactive glasses (BGs) are popular materials for scaffold production because of their tunable properties and ability to interact with the body for effective tissue regeneration. Due to their composition and amorphous structure, BGs possess a significant affinity with the recipient’s tissue. Additive manufacturing (AM), a method that allows th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 138 publications
(161 reference statements)
0
2
0
Order By: Relevance
“…It is reported that bioactive glass is used in bone tissue regeneration [ 224 , 225 , 226 ]. Recent studies have shown that the preparation of bioactive glass nanoparticles within the (SiO 2 -CaO-P 2 O 5 ) system can be specifically tailored for osteomyelitis treatments [ 227 , 228 , 229 ]. It is also reported that BG has other applications, including cancer treatment strategies like hyperthermia, phototherapy, and anticancer drug delivery, in which BG has demonstrated efficacy [ 230 , 231 , 232 ].…”
Section: Application Of Nanoparticles To Improve the Therapeutic Pote...mentioning
confidence: 99%
“…It is reported that bioactive glass is used in bone tissue regeneration [ 224 , 225 , 226 ]. Recent studies have shown that the preparation of bioactive glass nanoparticles within the (SiO 2 -CaO-P 2 O 5 ) system can be specifically tailored for osteomyelitis treatments [ 227 , 228 , 229 ]. It is also reported that BG has other applications, including cancer treatment strategies like hyperthermia, phototherapy, and anticancer drug delivery, in which BG has demonstrated efficacy [ 230 , 231 , 232 ].…”
Section: Application Of Nanoparticles To Improve the Therapeutic Pote...mentioning
confidence: 99%
“…Notably, polymer-ceramic composites stand out in these combinations by merging the toughness of polymers with the compressive strength of ceramics, resembling the properties of bone tissue. This leads to the development of bioactive scaffolds with impressive mechanical characteristics and favorable degradation rates [93,94].…”
Section: Compositesmentioning
confidence: 99%